The last of the Mochicans (Enhanced widescreen, 1992)
The Last of the Mohicans is a 1992 American epic historical drama film set in 1757 during the French and Indian War. It was written and directed by Michael Mann and was based on James Fenimore Cooper's 1826 novel The Last of the Mohicans: A Narrative of 1757 and George B. Seitz's 1936 film adaptation, owing more to the film than the novel. The film stars Daniel Day-Lewis, Madeleine Stowe, and Jodhi May, with Russell Means, Wes Studi, Eric Schweig, and Steven Waddington in supporting roles.